Analisis Pengaruh Budaya Keselamatan Pasien terhadap Pelaporan Insiden Keselamatan Pasien - Wahono Wahono; Sumeidi Kadarisman; Chevi Wirawan (Jurnal Pendidikan Indonesia, 2025)
The implementation of a patient safety culture in hospitals is crucial to reducing patient safety incidents. This culture serves as the foundation for achieving patient safety. This study aims to analyze the relationship between the patient safety culture and the reporting of patient safety incidents by healthcare workers at Surya Insani Hospital. The study design is quantitative with a cross-sectional approach. The research sample consists of 154 healthcare workers selected using purposive sampling. The patient safety culture with its 9 dimensions is considered the independent variable, while the reporting of patient safety incidents is the dependent variable. Data were collected using the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire and a patient safety incident reporting questionnaire developed by the researchers, and analyzed using multiple linear regression. The results indicate that the patient safety culture significantly affects the reporting of safety incidents, with F-value 95.986 > F-table 1.95 and Sig. 0.000 < 0.05. Partially, the expectations of supervisors, management support, teamwork, response to errors, open communication, and information handoff significantly influence reporting. In conclusion, a strong patient safety culture enhances the reporting of patient safety incidents by healthcare workers at Surya Insani Hospital.